RELIGIOUS PLURALISM IN ISLAM - Dr. Adnan Aslan (Journal of Islamic Thought and Civilization, 2011)
This paper is aimed at enumeration of some of the Quranic principles to suggest an account of 'Islamic pluralism'. The Quran accepts plurality as a natural phenomenon. Allah SWT states in the Quran: ―O Humankind! Verily we have created you of a male and female; and we have distributed you in nations and tribes that you might know one another and recognise that, in the sight of God the most honourable of you is the most pious. Verily God is wise and all knowing‖ (49:13). The aim of Islam is to integrate such diversity into unity through the sacred principles of the Quran; it explains the reason and purpose for such racial and religious multiplicity. After arriving in Medina, the Holy Prophet SAW introduced a new structure and value system which was connected through religion and citizenship instead of tribal links. He formed the constitution of Medina which stated the terms of relationships with Jews of Medina. The Prophet SAW extended the act of citizenship and co-operation to the Christians of Najran. The paper glances through Islamic history in order to identify a common official attitude of Muslim authority towards non-Muslim subjects.